Analysis and Optimization of Influencing Factors for Turnout Lateral Passing Performance of Rubber-tired Metro - DU Zixue; XU Chenyu; YANG Zhen; LIAO Congjian (Chengshi guidao jiaotong yanjiu)
［Objective］ In the turnout section, the wheel-rail relationship of the rubber-tired metro vehicle is relatively special as it is the rubber tire that provides running support and the steel wheel that provides guidance. In order to improve the operation quality of the rubber-tired metro vehicle, it is necessary to study the lateral passing performance of the turnout. ［Method］ Based on the new type of rubber-tired metro vehicle on Mexico City Metro Line 1, the running mechanism of the vehicle is analyzed, the dynamics model of the vehicle is established, and the evaluation index of the vehicle turnout lateral passing performance is proposed. Through analyzing the sensitivity of the vehicle main suspension parameters, their influencing coefficient on the evaluation index is obtained. The parameters with greater influence are optimized by using the non-dominated sorting genetic algorithm-II. ［Result & Conclusion］ With the vertical force of the running wheel, the lateral force of the guide wheel, the lateral force of the axle, the load transfer coefficient of the running wheel, and the roll angle of the car body as evaluation indexes, it is concluded that the vertical stiffness of air spring has the greatest impact on the turnout lateral passing performance of rubber-tired metro vehicles, followed by the damping of the vertical shock absorber and the radial stiffness of the guide wheel and etc. After optimization, the roll angle of the car body is reduced by 8.7%, and the load transfer coefficient of the running wheel by 16.0%. The vehicle can pass through the turnout at a speed of 45 km/h, and the turnout lateral passing performance of the vehicle is improved.